The Endless Road. On Writing The Road Less Travelled - Hildur Guðbergsdóttir 1984- (2015)
The Endless Road and On Writing The Road Less Travelled is a final assignment for a B.A. degree in English from the University of Iceland. The Endless Road is a novella is about a girl named Lia. At first glance, it would appear she is lucky, after all she has a loving girlfriend and is doing well in her studies at university. Everything changes with the arrival of her former lover Juliet who returns after an absence of six years. Juliet and Lia share a dark, haunting past and an unexpected turn of events is about to change their lives forever. Temptation also presents itself in the guise of beautiful detective Grace Morgan. The Road Less Travelled documents the evolution of The Endless Road; how it progressed from a mere idea to a novella. The essay furthermore explains how decisions were made regarding plot, character and setting. The essay was inspired by a real case which took place in New Zealand in 1954. The method chosen for writing required painstaking research and the results are described in The Road Less Travelled. The impact which the real life case had in its native New Zealand is examined in The Road Less Travelled and how murder came to be associated with homosexuality. Two girls committed a heinous murder in 1954 when women had not yet become associated with this brand of crime. The crime shocked a nation and inspired Peter Jackson to make his first movie, Heavenly Creatures. A scholarly book has been written on the case as well as a play called The Daughters of Heaven. The Endless Road and The Road Less Travelled provide fascinating insight into a case which impacted a nation and was called The Crime of the Century.